2008
DOI: 10.1016/j.ijrobp.2007.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Effect Relationships for the Submandibular Salivary Glands and Implications for Their Sparing by Intensity Modulated Radiotherapy

Abstract: Purpose-Submandibular salivary glands (SMGs) dysfunction contributes to xerostomia after radiotherapy (RT) of head and neck (HN) cancer. We assessed SMG dose-response relationships and their implications for sparing these glands by intensity modulated radiotherapy (IMRT).Patients and Methods-148 HN cancer patients underwent unstimulated and stimulated SMG salivary flow rate measurements selectively from Wharton's duct orifices, before RT and periodically through 24 months after RT. Correlations of flow rates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
150
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(159 citation statements)
references
References 50 publications
(51 reference statements)
5
150
1
3
Order By: Relevance
“…On the toxicity side, besides the attention given to spinal cord and brain stem (with toxicity thresholds of 45-50 Gy for the first and at 50 Gy for the second in most of the investigations), it is consolidated knowledge that, for parotids, mean doses inferior to [25][26][27][28][29][30] Gy correlate well with substantial recovery of function within two years (Li et al (4), Deasy et al (5)). Higher thresholds were observed for sub-mandibular glands in the range of 39 Gy by Murdoc et al (6), while a dose to oral cavity of about 30Gy for late mucositis was reported by Narayan et al (7). Recently, the wide application of IMRT allowed also investigations on strategies to reduce other common toxicity patterns.…”
Section: Introductionmentioning
confidence: 98%
“…On the toxicity side, besides the attention given to spinal cord and brain stem (with toxicity thresholds of 45-50 Gy for the first and at 50 Gy for the second in most of the investigations), it is consolidated knowledge that, for parotids, mean doses inferior to [25][26][27][28][29][30] Gy correlate well with substantial recovery of function within two years (Li et al (4), Deasy et al (5)). Higher thresholds were observed for sub-mandibular glands in the range of 39 Gy by Murdoc et al (6), while a dose to oral cavity of about 30Gy for late mucositis was reported by Narayan et al (7). Recently, the wide application of IMRT allowed also investigations on strategies to reduce other common toxicity patterns.…”
Section: Introductionmentioning
confidence: 98%
“…A mean dose (D mean ) of 39 Gy is the highest threshold dose reported to date. 6 The salivary flow was significantly reduced when the mean dose to the SMG was .39 Gy. Therefore, in this study, we set the restricted mean dose to the SMG at 39 Gy.…”
Section: Discussionmentioning
confidence: 92%
“…Taking the result of Murdoch-Kinch et al 6 as a reference, a limitation of D mean #39 Gy was added to SMGs in plans B, C and D, but the dose to PTVnx and PTV1 took priority over the limitation to SMGs. In addition, at least 95% of PTV-IIa in plan C and 90% of PTV-IIa in plan D had to have a 60 Gy covering.…”
Section: Treatment Planning and Optimizationmentioning
confidence: 99%
See 2 more Smart Citations